Prevention of Skin Disorders in Patients with Diabetes Mellitus Using Olive Oil in Semarang City - Suyanto, Suyanto; Muhammad Arifin Noor; Retno Setyawati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The high prevalence of diabetes mellitus (DM) leads to serious complications, including dry skin and diabetic foot wounds, which may progress to infection, ulcers, amputation, or even death if not properly managed. Diabetic foot wounds are the most common complications among DM patients, with a prevalence of 75%–90%. To address this issue, a community service program titled "Application of Olive Oil in Maintaining Healthy Skin in Diabetes Mellitus Patients" was conducted in December 2024 at RW 12, Bangetayu Kulon Village. The program aimed to improve knowledge and commitment among health cadres and residents in preventing and managing skin problems associated with DM. A total of 20 participants, including residents and health cadres, attended the event. It began with an assessment of the community’s limited knowledge about DM risks and diabetic foot wound care. The demographic analysis revealed that most participants were elderly (95.7%), predominantly male (52.2%), with high school education, and primarily engaged in entrepreneurial activities. Statistical analysis showed that education significantly improved participants’ understanding and commitment to diabetic foot skin care, with a p-value of 0.000 (p < 0.005). These findings demonstrate that targeted educational interventions effectively enhance awareness and skin care practices among DM patients. The success of this program highlights the potential for replicating similar initiatives in other communities to reduce DM-related complications and improve patient outcomes.